The applicability of a TRJ test in the diagnosis of children with complex speech disorders (the example of children with cleft lip and/or palate) - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2019)
This article analyses the applicability of the test called the TRJ test (Speech Development Test) to diagnose the language competence level of children with complex articulation disorders based on the example of children with cleft palate. The author shows the difficulties revealed during the test procedure in this group of children that arise or may result from articulation problems. Next, the conclusions from the TRJ test of the subject group of children for the construction of the test itself and for the person conducting the test resulting from own experience are presented. It is stated that despite the problems identified in this article related to the use of the TRJ test in the examination of children with complex articulation disorders, it is worth reaching for this diagnostic tool in the case of children with cleft palate, not only for speech therapy, but also for research purposes.